Analisis Pengaruh Tingkat Kesehatan Bank Dengan Metode CAMEL Terhadap Profitabilitas Pada Bank Konvensional Yang Tercatat Di BEI - Renanda Y.P, Helma (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This research is about the effect of Bank Soundness level which is measured using the CAMEL ratio with Profitability of Conventional Banks listed on the Indonesia Stock Exchange (IDX). In this study, the Capital is proxied by the CAR ratio, Earning is proxied by the NPL ratio, the Management is proxied by the NIM ratio, the Equity is proxied by the BOPO ratio, Liquidity is proxied by the LDR ratio, as a dependent variable, and profitability is proxied by ROA (Return on Assets) as an independent variable. The object of research in this study is Conventional Banks listed on the Indonesia Stock Exchange (IDX) in the period 2019-2021, with 30 Conventional Banks. The data of this research is from the annual financial reports of each bank. Which is processed by using the Multiple Linear Regression analysis. The result of research is that CAR affects profitability, this means that banks can manage capital to generate profits. NPL does not affect profitability because every year there are bad loans, so the NPL value is uncertain. NIM does not affect profitability because the bank can minimize bad loans with its productive assets. BOPO has a negative effect on profitability because with minimal costs it can generate maximum income. LDR has no effect on profitability because lending is not proportional to credit quality.